2019
DOI: 10.1016/j.anai.2019.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Association of antieosinophil therapy with decreased body mass index in patients with severe asthma

Abstract: The type 2 high endotype of asthma with adult onset is often characterized by severe, persistent, steroid-refractory eosinophilic inflammation. Interleukin 5 (IL-5) is a pivotal cytokine for eosinophil survival. The amelioration of eosinophilic inflammation through anti-IL-5 therapies (mepolizumab, reslizumab, and ben-ralizumab) reduces exacerbations and improves control is and well tolerated overall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…In humans, reducing or depleting eosinophils in asthma reduced body weight in thin and overweight asthma subjects 25,26 . Although these studies were not designed to test the role of eosinophils, this data does not support a protective role for eosinophils in obesity in humans.…”
Section: Reconciling Opposing Datamentioning
confidence: 88%
See 2 more Smart Citations
“…In humans, reducing or depleting eosinophils in asthma reduced body weight in thin and overweight asthma subjects 25,26 . Although these studies were not designed to test the role of eosinophils, this data does not support a protective role for eosinophils in obesity in humans.…”
Section: Reconciling Opposing Datamentioning
confidence: 88%
“…Kuruvilla et al. found in a small study, over 6 months, that anti‐IL‐5 therapy was associated with a mild but significant decrease in BMI in patients with severe asthma 25 . However, this particular study was not randomized or placebo controlled and lacked other measurements related to obesity including body fat and glucose tolerance 25 .…”
Section: Evidence That Eosinophils Do Not Reduce Obesitymentioning
confidence: 97%
See 1 more Smart Citation
“…The macrolide azithromycin could reduce the rate of exacerbation in adult patients with non-eosinophilic asthma [ 52 , 80 ]. Interestingly, a reduction in BMI was observed in asthma under anti-IL-5 therapy, which was associated with the role of eosinophils in the homeostasis of these cells in adipose tissue [ 83 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Initial data in adults have shown that metformin may also improve asthma exacerbations in patients with metabolic syndrome [ 86 ]. The role of anti-IL-5 therapy needs further evaluation [ 53 , 83 ], and an anti-IL-1 antibody is still being investigated in clinical trials [ 52 ]. Anti-thymic stromal lymphopoietin (TSLP) therapy, for example with tezepelumab, is also a possible approach [ 87 ].…”
Section: Treatmentmentioning
confidence: 99%